Membangun Kreativitas dan Ekonomi Masyarakat Desa Pasiran Melalui Pengolahan Keripik Pare - Nelly Nelly; Nurul Aziana (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
Pasiran Village is one of the areas in Bantan District, Bengkalis Regency, which is actively cultivating various plants through millennial farmer groups, one of which is bitter melon. Pare is a vegetable with a bitter taste and is less popular with the public, even though the properties contained therein are very many. So that the people in Pasiran Village are creative by processing bitter melon into delicious and tasty snacks, namely chips. This study aims to find out in depth about the processing of pare into chips and the marketing of processed bitter gourd chips to the community so as to improve the community's economy. This study used qualitative methods which were analyzed descriptively. The method of data collection is done by library research (library research). The results and discussion show that bitter melon chips are a creativity and innovation from the people of Pasiran Village to utilize agricultural products in their area. In addition, the large amount of nutritional content in bitter gourd makes people creative by making it a processed product to be consumed without the bitter taste, namely chips. Bitter gourd processing must be done correctly so that it is not bitter. The process of processing bitter gourd into chips also goes through very long stages. In addition, chip manufacturers also provide creations by adding flavor powder to bitter melon chips to attract consumers. The packaging process is also a matter of concern to attract consumer interest. While product marketing is done directly by word of mouth and in certain events. In addition, manufacturers also sell products through various social media platforms. Increasing the number of pare chip enthusiasts will have an impact on the economic progress of the Pasiran village community, especially the bitter melon chip producers